American Literary History (JSTOR)
Tables of contents for recent issues of American Literary History are available at http://www3.oup.co.uk/alhist/contents. Authorized users may be able to access the full text articles at this site.Recent Americanist scholarship has generated some of the most forceful responses to questions about literary history and theory. Yet too many of the most provocative essays have been scattered among a wide variety of narrowly focused publications. Covering the study of U.S. literature from its origins through the present, American Literary History provides a much-needed forum for the various, often competing voices of contemporary literary inquiry.
Keywords: American Studies